Theoretical Basis for Switching a Kramers Single Molecular Magnet by Circularly-Polarized Radiation - Maryasov, Alexander G. (Materials (Basel), 2019)
The d-group Kramers ions, having strong zero field splitting (ZFS) with axial symmetry and a negative D value for the ZFS Hamiltonian, are widely considered as candidates for use as single molecular magnets (SMMs). An important need is the means to switch the SMM between its states in a reasonably short and predictable period of time, which is generally not available. We propose an approach, Zeeman–far infrared (ZeFIR) double resonance, in which circularly polarized alternating magnetic fields in the far infrared (FIR) range induce selective magnetic dipole transitions between different Kramers doublets of the SMM and polarized microwave (mw) pulses transfer excitation inside the upper Kramers doublet. A combination of FIR and mw pulses allows unidirectional switching between +S and −S states of the ion. The proposed approach is considered for a model quartet system with total spin S = 3/2, which seems to be the most promising object for selective resonance manipulations of its states by circularly polarized radiation.